MODEL PEMBELAJARAN INTEGRATIF AGAMA DAN SAINS UNTUK MEMBENTUK KARAKTER RELIGIUS SISWA SEKOLAH DASAR INTEGRAL KOTA PROBOLINGGO - Khoiriyah; Benny Prasetiya; Ahsan Hakim (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The separation between religion and science in primary school learning often leads students to perceive science merely as empirical knowledge, while religion is positioned as a normative doctrine detached from their learning experiences. This condition highlights the need for a learning model that integrates scientific literacy, religious reflection, and character formation within a unified pedagogical framework. This study aims to analyze the implementation of an Integrative Religion and Science Learning Model in shaping the religious character of students at an Integrated Primary School in Probolinggo City. The study employed a mixed-method approach with a sequential explanatory design. Quantitative data were collected through questionnaires administered to fifth-grade students to examine the relationship between the implementation of the integrative learning model and students’ religious character. Qualitative data were obtained through classroom observations and interviews with teachers and students to explain the learning processes, contextual dynamics, and pedagogical meanings underlying the model. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and thematic analysis, and were subsequently integrated through a joint display. The findings indicate that the integrative religion and science learning model is implemented through the integration of learning objectives, science content and religious values, inquiry-reflective activities, and religious habituation within the school environment. The model contributes to the formation of students’ religious character through the strengthening of faith, worship practices, moral conduct, gratitude, responsibility, and social care. This study emphasizes that religious character formation cannot rely solely on verbal religious instruction but should be developed through science learning that is reflective, dialogical, and spiritually meaningful.